1988
DOI: 10.1139/v88-318
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions in adamantane derivatives: 2-chloroadamantane

Abstract: Thispaper is dedicated to Professor Charles A. McDowell on the occasion of his seventieth birthdayRALPH M. PAROLI, NANCY T. KAWAI, IAN S. BUTLER, and DENIS F. R. GILSON. Can. J. Chem. 66, 1973 (1988. The phase transition behaviour of 2-chloroadamantane, 2-CloHlsC1, has been investigated by differential scanning calorimetry (DSC), and FT-IR and Raman spectroscopy. Two transitions were detected by both DSC and vibrational spectroscopy at 23 1 and 178 K, on cooling, and at 242 and 227 K, on heating. The measurede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Although the number of studies concerning 2-X-adamantane derivatives is less extensive, detailed polymorphic studies have also been reported. [15][16][17][18][19][20][21][22] The phase behavior of the 1-X adamantane compounds varies according to the substituent.…”
Section: Introductionmentioning
confidence: 99%
“…Although the number of studies concerning 2-X-adamantane derivatives is less extensive, detailed polymorphic studies have also been reported. [15][16][17][18][19][20][21][22] The phase behavior of the 1-X adamantane compounds varies according to the substituent.…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour of fluoroadamantane under pressure also remains unexplored, and, due to the apparent disorder down to 4 K, the effect of pressure may be different from the effects that result from lowering the temperature. Thus, as an extension of previous studies on the chloro and bromo derivatives (17)(18)(19), the phase behaviour of fluoroadamantane was investigated by low-temperature and high-pressure vibrational spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state phase transitions of halogen-substituted adamantanes below the reference temperature 298.15 K has been a popular endeavor in the recent literature. Calorimetric studies of 1-Cl-adamantane [7,8], 2-Cl-adamantane [9,10], 1-Br-adamantane [7,[11][12][13], and 2-Br-adamantane [10] are already published in the literature and the available enthalpies of phase transitions are mostly in agreement within 1 kJ·mol -1 . In contrast, the solid-gas phase transitions of halogen-substituted adamantanes are reported only in three papers [11,[14][15] and reported sublimation enthalpies seem to be in disarray.…”
Section: Introductionmentioning
confidence: 91%